RETRACTED: Solving the forecasting demand for specialists problem using fuzzy logic methods - Sergiyanskiy Evgeniy; Kirillov Ivan; Smirnova Alena (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001